2008
DOI: 10.1016/j.ejcb.2008.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-based proteomic profiling of aged skeletal muscle: Decreased pyruvate kinase isozyme M1 exhibits drastically increased levels of N-glycosylation

Abstract: Since various neuromuscular diseases are associated with abnormal glycosylation, it was of interest to determine whether this key post-translational modification is also altered in aged skeletal muscle. Lectins represent highly versatile carbohydrate-binding proteins that are routinely employed for the characterization of glycoproteins. Here, we used the lectin wheat germ agglutinin (WGA) for the proteomic profiling of senescent fibers. WGA labeling of the soluble proteome from 3-month-versus 30-month-old rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 74 publications
2
34
0
Order By: Relevance
“…Pyruvate isoform PK-M1 exists as 5 sub-species with differing isoelectric points in skeletal muscle tissues, whereby theses isozymes display varying degrees of phosphorylation and glycosylation [21,24]. Previous studies have clearly shown that the PK isoform exhibiting a pI of 6.6 and an apparent molecular mass of 57.8 kDa is several-fold decreased in senescent muscle fibres [21]. Other PK forms with a more acidic or basic pI-value did not show major alterations in concentration levels between crude total protein extracts from young versus aged muscle [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pyruvate isoform PK-M1 exists as 5 sub-species with differing isoelectric points in skeletal muscle tissues, whereby theses isozymes display varying degrees of phosphorylation and glycosylation [21,24]. Previous studies have clearly shown that the PK isoform exhibiting a pI of 6.6 and an apparent molecular mass of 57.8 kDa is several-fold decreased in senescent muscle fibres [21]. Other PK forms with a more acidic or basic pI-value did not show major alterations in concentration levels between crude total protein extracts from young versus aged muscle [18].…”
Section: Discussionmentioning
confidence: 99%
“…These proteomic profiling studies have focused on crude soluble extracts and have shown that muscle aging is associated with altered expression levels of many key contractile proteins, regulatory elements, ion handling proteins, metabolic enzymes and mediators of the cellular stress response [14][15][16][17][18][19][20]. The proteomic finding of a drastically decreased density and reduced enzymatic activity of certain glycolytic enzymes in senescent fibres [21] is in agreement with the idea of a fast-to-slow transformation process during aging [13]. In analogy, proteomic surveys clearly revealed increased levels of mitochondrial enzymes and metabolite transporters of aerobic metabolism in aged muscle [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteomic profiling of crude soluble extracts has revealed a severely perturbed protein expression pattern in aged muscles involving enzymes of various metabolic pathways, regulatory components of ion homeostasis and elements of the cellular stress response (Piec et al, 2005;Gelfi et al, 2006;O'Connell et al, 2007;Doran et al, 2008;Lombardi et al, 2009;Capitanio et al, 2009). Altered post-translational modifications affecting tyrosine nitration, tyrosine/threonine phosphorylation and N-glycosylation were recently documented to occur to a large extent during biological aging of skeletal muscle fibres (Kanski et al, 2005;Gannon et al, 2008;O'Connell et al, 2008b). The proteomic finding that the ratelimiting glycolytic enzyme pyruvate kinase is greatly reduced in aged muscle, while the expression of key mitochondrial proteins is increased in sarcopenia, strongly suggests a shift towards a more aerobicoxidative metabolism in senescent muscle fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Protein profiling of whole tissue homogenates has been performed using twodimensional gel electrophoresis (2DGE) 1 and mass spectrometry to identify the proteins differentially expressed during aging in rat (4 -6) and human muscle (7,8). Other studies have focused on specific fractions such as mitochondrial proteins (9), phosphoproteins (10), glycoproteins (11), basic proteins (12), or calpain interacting proteins (13). The few proteomic studies available on human skeletal muscle are mostly based on the 2DGE approach, which implies focusing on a specific pH range (7,8).…”
mentioning
confidence: 99%